Frequency of Parenternal Exposure and Seroprevelence of HBV, HCV and HIV among Operating Room Personnel - Qudrat Ullah; Usman Ali Rehman; Asif Hanif (The International Journal of Frontier Sciences, 2018)
Background: There are many experiences in the operation theatre professionals to get Hepatitis B virus, Hepatitis C virus and Human immunodeficiency virus during their profession in operating room due to accidental needle pricks or through cut by any sharp. The objective of this study is to find out the Frequency of parenteral exposure and seroprevelence of HBV, HCV and HIV among operating room personnel. Methodology: Frequency of parenteral exposure and seroprevalence of HBV, HCV and HIV among operating room personnel was found using ICT method. Results: All 108 (100 %) operating room personnel were HBV, HCV and HIV negative, none of them showed positive results. Among these 108 operating room personnel to complete my research, among these 58 (53.7%) were male and 50 (46.3%) were female. Conclusion: It is concluded by the study that there are no positive cases of HBV, HCV and HIV among operating room personnel in Gulab devi hospital and Masood hospital.